THE CONCEPT OF CULTURE AND THE REREADING OF HIND SWARAJ - Pandey, Krishna Chand (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The concept of culture is explained through the concept of self. The self divides itself into the duality of subject and subjected. Its being a subject is being conscious, the culmination of which is its existence in the form of truth-consciousness-bliss where the difference of duality vanishes and the subjected or the person-oriented self dissolves and is established in the uni-versal self.